In-situ fatigue experiment device suitable for Ti2AlNb material and experiment method thereof

By designing a micro-nano-size in-situ bending fatigue experimental device suitable for Ti2AlNb materials, using electron microscope and focused ion beam technology, the bending fatigue test of micron-scale samples was realized, solving the problem of difficult testing in the existing technology and improving the test The sample fixation and processing accuracy were used to obtain the microscopic mechanism analysis of the bending fatigue damage of the sample.

CN119309914APending Publication Date: 2025-01-14AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411386074.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing micro-nano bending fatigue experimental devices are difficult to achieve in-situ bending fatigue testing of Ti2AlNb alloy materials at the micrometer scale, resulting in insufficient theoretical understanding of its deformation and failure mechanism.

Method used

A micro-nano-size in-situ bending fatigue experimental device including an electron microscope in-situ testing system, a fixed fixture and a force sensor was designed. The in-situ SEM image of the sample during the bending fatigue process was obtained through the electron microscope device, using J-shaped grooves and The mating of the connecting part is connected to fix the sample, and a bending load perpendicular to the length of the sample is applied by a loading drive mechanism, and the sample is prepared in conjunction with focusing ion beam processing.

Benefits of technology

The bending fatigue test of micron-scale Ti2AlNb samples was realized, which simplified sample fixation, reduced sliding possibility, ensured the compactness and connection stability of the sample structure, improved the sample processing accuracy and surface quality, and obtained Micromechanism analysis of the deformation and failure of the specimen during bending fatigue damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119309914A_ABST
    Figure CN119309914A_ABST
Patent Text Reader

Abstract

The invention discloses a micro-nano size in-situ bending fatigue experiment research device suitable for a Ti2AlNb material and an experiment research method of the micro-nano size in-situ bending fatigue experiment research device, and belongs to the technical field of micro-nano mechanics experiments. The experimental device comprises an electron microscope in-situ testing system, a fixing clamp, a loading driving mechanism and a force sensor, the electron microscope in-situ test system comprises a base, a sample table and electron microscope equipment, the sample table is fixedly arranged on the base, and a fixing clamp is movably arranged on the base; the sample table and the fixing clamp are correspondingly arranged at intervals, the distance between the fixing clamp and the base is smaller than that between the sample table and the base, so that a sample is connected between the sample table and the fixing clamp, and the length direction of the sample is parallel to the sample table; the fixing clamp is connected with the loading driving mechanism and is used for applying a bending load perpendicular to the axis of the sample to the sample; the force sensor is connected between the fixing clamp and the loading driving mechanism and is used for detecting the loaded bending load; and the electron microscope equipment is used for synchronously obtaining an in-situ SEM image of the sample.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of micro-nanomechanics experimental technology, and in particular to a method suitable for Ti 2 Micro-nano scale in-situ bending fatigue experimental research device and experimental research method for AlNb materials. Background Art

[0002] Micro-nano bending fatigue experiments are extremely difficult. Existing in-situ experiments mostly focus on the mechanical response and plastic deformation characteristics of micro-nano metal copper and other materials under quasi-static loads, and rarely involve the bending fatigue damage process of materials.

[0003] Micro-nanoscale in-situ bending fatigue mechanical experimental testing is extremely challenging, and existing experimental devices and methods are difficult to achieve bending fatigue testing of micron-scale alloy materials, resulting in the 2 There is insufficient theoretical understanding of the microscopic mechanisms of deformation and failure of AlNb alloy materials. Summary of the invention

[0004] In view of the above analysis, the embodiment of the present invention is to provide a method suitable for Ti 2 The micro-nano-scale in-situ bending fatigue experimental research device and experimental research method of AlNb materials are used to solve the problem that existing experimental devices and methods are difficult to achieve micron-scale Ti 2 Problems in in-situ bending fatigue testing of AlNb alloy materials.

[0005] On the one hand, embodiments of the present invention provide a method suitable for Ti 2 The micro-nano-size in-situ bending fatigue experimental research device of AlNb material comprises: an electron microscope in-situ testing system, a fixing fixture, a loading driving mechanism and a force sensor; the electron microscope in-situ testing system comprises: a base, a sample stage and an electron microscope device, the sample stage is fixedly arranged on the base, and the fixing fixture is movably arranged on the base; the sample stage and the fixing fixture are arranged at intervals corresponding to each other, and the distance between the fixing fixture and the base is smaller than the distance between the sample stage and the base; the sample stage has a bearing surface perpendicular to the base, one end of the sample is connected to the bearing surface of the sample stage, and the other end extends toward the base in a direction parallel to the bearing surface and is connected to the fixing fixture, so as to load the Ti 2 The sample of AlNb material is connected between the sample stage and the fixing fixture, and the length direction of the sample is parallel to the load-bearing surface; the end of the fixing fixture away from the sample stage is connected to the loading drive mechanism, which is used to drive the fixing fixture to move back and forth in a direction perpendicular to the load-bearing surface to apply a bending load perpendicular to the length direction of the sample to the sample; the force sensor is connected between the fixing fixture and the loading drive mechanism, which is used to detect the applied bending load; the electron microscope equipment is used to synchronously obtain the in-situ SEM image of the sample during the bending fatigue test.

[0006] Further, a loading end is formed at one end of the fixing fixture close to the sample stage, and a J-shaped groove is formed at a side of the loading end away from the base, and an opening of the J-shaped groove is arranged at a side of the loading end away from the base and perpendicular to the sample stage bearing surface; the J-shaped groove includes a first limiting groove, a second limiting groove and a third limiting groove connected in sequence, and the length direction of the second limiting groove is perpendicular to the sample stage bearing surface;

[0007] The sample includes a sample body and a connecting portion, the connecting portion is J-shaped, the sample stage is used to fix the sample body, the connecting portion includes a first connecting section, a second connecting section and a third connecting section, the first connecting section is connected to the sample body, the first connecting section is parallel to the third connecting section, and the second connecting section is vertically connected between the first connecting section and the third connecting section; when the sample is connected to the sample stage, the connecting portion is located on the side of the sample stage facing the base, and the second connecting section is perpendicular to the bearing surface; wherein the J-shaped groove matches the shape and size of the connecting portion, and the J-shaped groove is used to install the connecting portion.

[0008] Furthermore, the loading end includes a main body and an extension part. The main body is in a truncated cone shape, and the central axis of the main body is perpendicular to the bearing surface of the sample stage. One end of the main body is connected to the loading drive mechanism, and the other end is fixedly connected to the extension part. The extension part is rectangular, and a J-shaped groove is formed on the side of the extension part away from the base.

[0009] Furthermore, the length of the first connecting segment is 10-14 μm, the total length of the second connecting segment is 7.5-10.5 μm, and the length of the third connecting segment is 3.8-5.3 μm.

[0010] Furthermore, the length of the first connecting segment is 3.9 to 4.1 times the width of the second connecting segment, the total length of the second connecting segment is 1.9 to 2.1 times the length of the third connecting segment, and the length of the third connecting segment is 1.5 to 1.7 times the width of the second connecting segment.

[0011] On the other hand, an embodiment of the present invention provides a method suitable for Ti 2 The micro-nano-scale in-situ bending fatigue experimental research method of AlNb material is implemented by using the experimental device of the above embodiment, which includes:

[0012] Step S1, preparation of Ti 2 A sample of AlNb material is mounted on a sample stage of an experimental device, wherein a length direction of the sample is parallel to the sample stage, and a J-shaped connecting portion of the sample extends out of the sample stage and toward the base;

[0013] Step S2, moving the fixing fixture of the experimental device so that the connecting portion of the sample is connected to the J-shaped groove of the loading end of the experimental device; wherein the J-shaped groove is arranged on the side of the loading end away from the base, and its opening direction is away from the base and perpendicular to the sample stage;

[0014] Step S3, starting the loading drive mechanism to drive the fixing fixture to move back and forth in a cyclic direction perpendicular to the sample stage bearing surface, so as to cyclically load the sample with a bending load perpendicular to the length direction of the sample, and at the same time collect data from the force sensor, and collect in-situ SEM images of the sample during the cyclic loading process;

[0015] Step S4, analyzing the deformation and bending fatigue failure behavior of the sample under cyclic load based on the data of the force sensor and the SEM image.

[0016] Further, step S1 includes: using a focused ion beam to remove the Ti 2 A microblock is cut out from a selected area of ​​the AlNb material; the microblock is fixed on a supporting copper stage in a focused ion beam-scanning electron microscope dual beam system; the microblock is milled by a focused ion beam to gradually process the sample into a sample, the formed sample including a sample body and a J-shaped connecting portion; the supporting copper stage is connected to the sample stage.

[0017] Furthermore, the focused ion beam milling of the microblock includes: using the focused ion beam to sequentially perform rough processing and fine processing on the microblock; wherein the ion beam current during the rough processing is 20-40nA, and the ion beam current during the fine processing is 40-60pA.

[0018] Furthermore, in step S1, the microblock is fixed on the copper support platform, including: depositing metal platinum between the microblock and the copper support platform to fix the microblock on the copper support platform, and the deposition thickness of the metal platinum is 18-25 nm.

[0019] Furthermore, when depositing metal platinum, the deposition current is 40-60 pA and the deposition voltage is 20-30 kV.

[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0021] 1. Using the experimental research device and experimental research method of the present invention, the micron-scale Ti 2 The AlNb sample is mounted on the sample table. Through the connection between the sample and the fixing fixture, the loading drive mechanism can perform cyclic loading of the bending load on the sample. At the same time, the in-situ SEM image during the cyclic loading process is obtained through the electron microscope equipment, which is convenient for studying and analyzing Ti 2 Microscopic mechanism of deformation and failure of AlNb specimens during bending fatigue damage.

[0022] 2. The present invention is simple to operate by matching the J-shaped connecting portion of the specimen with the J-shaped groove on the fixing fixture, and can easily and firmly fix the specimen, thereby reducing the possibility of the specimen sliding during the bending load loading process.

[0023] 3. The present invention limits the size of the sample within a suitable range, which not only maintains the compactness of the sample structure and occupies a smaller space, but also ensures the stability of the connection between the sample and the fixing fixture, avoiding the sample from falling out during the bending fatigue test and local deformation of the contact area, which may affect the test results.

[0024] 4. The present invention can ensure the processing accuracy of the sample and improve the quality of the surface of the sample by controlling parameters such as the ion beam current and the deposition current of metal platinum during sample preparation within a suitable range; by controlling the deposition thickness of metal platinum, it can ensure that the sample is firmly connected to the sample stage and avoid increasing the surface roughness of the sample.

[0025] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the embodiments of the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The drawings are only for the purpose of illustrating specific embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0027] Figure 1 Schematic diagram of the structure of a micro-nano-sized in-situ bending fatigue experimental research device according to some embodiments of the present invention.

[0028] Figure 2 for Figure 1 Schematic diagram of the structure of the loading end.

[0029] Figure 3 Schematic diagram of the structure of the sample connection part of some embodiments of the present invention.

[0030] Figure 4 Schematic diagram of the process of preparing samples according to some embodiments of the present invention.

[0031] Figure 5 This is a schematic diagram of the structure of the sample of Example 1 of the present invention.

[0032] Figure 6 This is a schematic diagram of a loading function curve of Example 1 of the present invention. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of the present invention clearer, exemplary embodiments of the present invention will be described below in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. For the sake of clarity and conciseness, not all features of the actual implementation are described in the specification.

[0034] The embodiment of the present invention provides a method suitable for Ti 2 Micro-nano-scale in-situ bending fatigue experimental research device for AlNb materials, such as Figure 1 As shown, the experimental research device includes: an electron microscope in-situ testing system, a fixing fixture 3, a loading drive mechanism (not shown in the figure) and a force sensor 4.

[0035] The electron microscope in-situ test system comprises: a base 1, a sample stage 2 and an electron microscope device (not shown in the figure), wherein the sample stage 2 is fixedly arranged on the base 1, and the fixing fixture 3 is movably arranged on the base 1; wherein the sample stage 2 and the fixing fixture 3 are arranged at intervals corresponding to each other, and the distance between the fixing fixture 3 and the base 1 is smaller than the distance between the sample stage 2 and the base 1, so as to 2 The sample 10 of AlNb material is connected between the sample stage 2 and the fixing fixture 3. The sample stage 2 is used to support the sample 10 with a bearing surface perpendicular to the base 1, wherein one end of the sample 10 is connected to the bearing surface of the sample stage 2, and the other end extends toward the base 1 in a direction parallel to the bearing surface and is connected to the fixing fixture 3, so that the length direction of the sample 10 is parallel to the bearing surface of the sample stage 2 (that is, perpendicular to the base).

[0036] The end of the fixing fixture 3 away from the sample stage 2 is connected to the loading drive mechanism, and the loading drive mechanism is used to drive the fixing fixture 3 to move back and forth in a direction perpendicular to the bearing surface of the sample stage 2, so as to apply a bending load perpendicular to the bearing surface of the sample stage to the end of the sample 10 connected to the fixing fixture 3, that is, to apply a bending load perpendicular to the length direction of the sample 10, so that the end of the sample 10 connected to the fixing fixture 3 can bend in two directions in a cyclical reciprocating manner, that is, bend in the direction toward and away from the bearing surface of the sample stage 2.

[0037] The force sensor 4 is connected between the fixing fixture 3 and the loading drive mechanism to detect the loaded bending load; the electron microscope equipment is used to synchronously obtain the in-situ SEM image of the sample 10 during the bending fatigue test.

[0038] Using the experimental research device of the present invention, the micron-scale Ti 2 The AlNb sample is mounted on the sample table. Through the connection between the sample and the fixing fixture, the loading drive mechanism can perform cyclic loading of the bending load on the sample. At the same time, the in-situ SEM image during the cyclic loading process is obtained through the electron microscope equipment, which is convenient for studying and analyzing Ti 2Microscopic mechanism of deformation and failure of AlNb specimens during bending fatigue damage.

[0039] In some embodiments, the electron microscope in-situ testing system can adopt an existing in-situ testing system, such as a Bruker electron microscope dedicated in-situ nanomechanical testing system, and the base 1, sample stage 2, and electron microscope equipment are all the original base and sample stage of the system.

[0040] In an embodiment of the present invention, a loading drive mechanism can be used to drive the fixed clamp to move back and forth in a direction perpendicular to the length of the sample, thereby pushing and pulling the loading end to move in a cyclical and reciprocating manner, and then applying tension and pressure perpendicular to its length direction to the sample, so that the sample is subjected to force and bends and deforms in a direction away from and toward the bearing surface of the sample table 2, thereby realizing a bending fatigue test of the sample.

[0041] In some embodiments, the force sensor can detect the magnitude of the tension and pressure applied by the loading drive mechanism, so as to control the loading degree of the loading drive mechanism according to the detection data of the force sensor, thereby ensuring the accuracy of the experiment; at the same time, it is convenient to analyze the bending fatigue failure behavior of the sample according to the detection data. Specifically, the raw data acquisition rate of the force sensor is 200 Hz.

[0042] like Figure 1 and Figure 2 As shown, in some embodiments, a loading end 5 is formed at one end of the fixing fixture 3 close to the sample stage 2, and a J-shaped groove 53 is formed at the side of the loading end 5 away from the base 1. Specifically, the opening of the J-shaped groove 53 is located at the side of the loading end 5 away from the base 1 and perpendicular to the bearing surface of the sample stage 2, and the J-shaped groove 53 includes a first limiting groove, a second limiting groove and a third limiting groove, the first limiting groove is parallel to the third limiting groove, and the second limiting groove is perpendicular to the first limiting groove and the second limiting groove respectively. Among them, the length direction of the second limiting groove is perpendicular to the bearing surface of the sample stage 2.

[0043] Correspondingly, such as Figure 1 and Figure 4 As shown, the sample 10 includes a sample body 11 and a connecting portion 12, the connecting portion 12 is J-shaped, the sample stage 2 is used to fix the sample body 11 and extend the connecting portion 12 toward the base 1, the J-shaped groove 53 matches the connecting portion 12, and the J-shaped groove 53 is used to install the connecting portion 12.

[0044] Specifically, Figure 3As shown, the connection portion 12 of the sample 10 includes a first connection segment a, a second connection segment b and a third connection segment c, the first connection segment a is connected to the sample body 11, the first connection segment a is parallel to the third connection segment c, and the second connection segment b is vertically connected between the first connection segment a and the third connection segment c. When the sample 10 is connected to the sample stage 2, the first connection segment a and the third connection segment c of the connection portion 12 are parallel to the bearing surface of the sample stage 2, and the second connection end b is vertical to the bearing surface of the sample stage, so that the connection portion 12 is matched and connected with the J-shaped groove.

[0045] During the bending fatigue test, when a bending load perpendicular to the bearing surface of the sample stage 2 is applied to the sample, the J-shaped groove is matched with the J-shaped connecting portion 12 of the sample, and the first limiting groove and the third limiting groove are used to limit the sliding of the connecting portion 12 in the vertical direction of the bearing surface of the sample stage 2, and the second limiting groove is used to limit the sliding of the connecting portion 12 in the parallel direction of the bearing surface of the sample stage 2, thereby ensuring a stable connection between the sample and the fixing fixture.

[0046] The embodiment of the present invention is simple to operate through the matching connection between the J-shaped connecting part of the specimen and the J-shaped groove on the fixing fixture, and can simply and firmly fix the specimen, thereby reducing the possibility of sliding of the specimen during the bending load loading process, ensuring high-quality contact between the specimen and the loading end, avoiding the influence of local deformation of the contact area between the specimen and the loading end on the bending loading process of the specimen, and improving the accuracy of the experiment.

[0047] like Figure 2 As shown, in some embodiments, the loading end 5 includes a main body 51 and an extension portion 52, the main body 51 is in a truncated cone shape, the central axis of the main body 51 is perpendicular to the bearing surface of the sample stage 2, one end of the main body 51 is connected to the loading drive mechanism, and the other end is fixedly connected to the extension portion 52, the extension portion 52 is rectangular, and a J-shaped groove 53 is formed on the side of the extension portion 52 that is perpendicular to the bearing surface of the sample stage 2 and away from the base 1, so that the connecting portion 12 of the sample 10 can be connected to the J-shaped groove 53 of the loading end 5, so that the sample 10 is connected between the sample stage 2 and the fixing fixture 3 along a direction parallel to the bearing surface of the sample stage 2, and a bending load perpendicular to the length direction of the sample can be applied to it when the loading drive mechanism moves, so as to achieve the Ti 2 Bending fatigue test of AlNb specimens.

[0048] In some embodiments, the loading end 5 is integrally formed at one end of the fixing fixture 3 and is machined at the end of the fixing fixture 3. By machining the extension portion 52 at the end of the loading end 5, the J-shaped groove 53 is obtained.

[0049] In some embodiments, the length of the first connecting segment a is 10-14 μm and the width is 2.5-3.5 μm; the total length of the second connecting segment b is 7.5-10.5 μm and the width is 2.5-3.5 μm; the length of the third connecting segment c is 3.8-5.3 μm.

[0050] The present invention limits the size of the sample within a suitable range, which not only maintains the compactness of the sample structure so that it occupies a smaller space and is convenient for in-situ bending fatigue testing of the sample in the experimental device; it also ensures the stability of the connection between the sample and the fixing fixture, avoiding the sample from falling out during the bending fatigue test and local deformation of the contact area, which may affect the experimental results.

[0051] Furthermore, the length of the first connecting section is 3.9 to 4.1 times the width of the second connecting section, the total length of the second connecting section is 1.9 to 2.1 times the length of the second straight section, and the length of the third connecting section is 1.5 to 1.7 times the width of the second connecting section. The embodiments of the present invention effectively improve the structural strength of the sample and the stability of the connection with the fixing fixture by limiting the proportions of the various parts of the sample within a reasonable range, and facilitate specific size design according to specific needs in different scenarios.

[0052] In some embodiments, transition fillets are provided at the connection points between the second connection segment and the first connection segment and the third connection segment to reduce stress concentration at the sharp corners and further improve the structural strength and stability of the sample. Specifically, the fillet radius is 0.5 μm.

[0053] In addition, an embodiment of the present invention also provides a method suitable for Ti 2 The micro-nano-scale in-situ bending fatigue experimental research method of AlNb material can be implemented using the experimental device of the above embodiment. The experimental method specifically includes the following steps:

[0054] Step S1, preparation of Ti 2 A sample of AlNb material is installed on a sample stage of an experimental device, wherein the length direction of the sample is parallel to the sample stage, and a J-shaped connecting portion of the sample extends out of the sample stage and toward the base, and a recessed opening of the J-shaped connecting portion faces the sample stage;

[0055] Step S2, moving the fixing fixture of the experimental device so that the connecting portion of the sample is connected to the J-shaped groove of the loading end of the experimental device; wherein the J-shaped groove is arranged on the side of the loading end away from the base, and its opening direction is away from the base and perpendicular to the sample stage;

[0056] Step S3, starting the loading drive mechanism to drive the fixing fixture to move back and forth in a cyclic direction perpendicular to the sample stage bearing surface, so as to cyclically load the sample with a bending load perpendicular to the length direction of the sample, and at the same time collect data from the force sensor, and collect in-situ SEM images of the sample during the cyclic loading process;

[0057] Step S4, analyzing the deformation and bending fatigue failure behavior of the sample under cyclic load based on the data of the force sensor and the SEM image.

[0058] The experimental method of the present invention is to micron-scale Ti 2 The AlNb sample is mounted on the sample stage and connected to the J-slot at the loading end through the connecting part of the sample. The loading drive structure is used to drive the fixed fixture to move, and then drive the loading end to move, so as to perform cyclic loading of the bending load on the sample, and then obtain the in-situ SEM image of the sample in the fatigue bending fatigue test.

[0059] In some embodiments, preparing the sample and installing the sample on the sample stage in step S1 specifically includes the following steps:

[0060] Using focused ion beam (FIB) from Ti 2 Microblocks are cut out from selected areas of the AlNb material;

[0061] In a focused ion beam-scanning electron microscope dual beam (FIB-SEM) system, the microblock was fixed on a copper support stage;

[0062] The microblock is milled by focused ion beam to gradually shape the sample into a sample, and the molded sample includes a sample body and a J-shaped connecting part;

[0063] Connect the copper support to the sample stage.

[0064] The preparation method in the embodiment of the present invention is used to mill Ti by focusing ion beam processing. 2 AlNb material can obtain samples of desired shape and micron scale.

[0065] In some embodiments, the microblock is milled by a focused ion beam, including: using a focused ion beam to sequentially perform rough processing and fine processing on the microblock, wherein the ion beam current during the rough processing is 20 to 40 nA, for example, 20 nA, 30 nA, 40 nA, preferably 30 nA; the ion beam current during the fine processing is 40 to 60 pA, for example, 40 pA, 50 pA, 60 pA, preferably 50 pA.

[0066] The embodiment of the present invention adopts an appropriate range of ion beam current to Ti 2 The AlNb material is processed roughly, which can quickly remove the excess material in the early stage and save preparation time; then the Ti2 Fine machining of AlNb materials can improve machining accuracy and sample surface quality, ensuring that micrometer-scale samples of the required size are obtained. At the same time, the sample surface is flat and smooth, which is convenient for observing sample surface cracks in SEM images, and for identifying and segmenting different features of the sample surface, making the analysis results more reliable.

[0067] In addition, the working voltage of the focused ion beam is 20-30 kV, which can ensure the processing depth and processing rate while maintaining a certain imaging quality and processing accuracy of the sample, and is suitable for micron-scale Ti 2 Precision machining of AlNb materials. Preferably, the operating voltage is 30 kV.

[0068] For Ti in the embodiment of the present invention 2 For AlNb materials, under the above working voltage and fine-processed ion beam current, the processing accuracy can reach nanometer level, specifically about 10nm; the roughness of the sample surface can reach Ra10nm, or even Ra1nm.

[0069] In some embodiments, in step S1, fixing the microblock on the copper support platform includes: depositing metal platinum between the microblock and the copper support platform to fix the microblock on the copper support platform, and the deposition thickness of the metal platinum is 18-25 nm. Preferably, the deposition thickness is 20 nm.

[0070] The embodiments of the present invention can ensure that the metal platinum can firmly adhere the microblocks to the supporting copper platform by controlling the deposition thickness of the metal platinum within a suitable range, while preventing the metal platinum from being too thick, which may affect the subsequent processing accuracy and increase the surface roughness of the sample.

[0071] In some embodiments, when depositing metal platinum, the deposition current is 40-60pA, preferably 50pA; the deposition voltage is 20-30kV. The embodiments of the present invention use an extremely low deposition current (picoampere level) for Pt deposition, which can provide more precise deposition control and avoid damage to the sample and thermal effects caused by excessive current, especially in the fine deposition process of the present invention with extremely small deposition thickness.

[0072] Specifically, when preparing and installing the sample in step S1, Figure 4 As shown, the specific process includes the following:

[0073] (1) Figure 4 As shown in (a), FIB is used to obtain Ti 2 Cut out microblocks 13 in selected areas of the AlNb material;

[0074] (2) Figure 4As shown in (b), in the FIB-SEM dual beam system, the robot arm 20 is micro-welded to the upper surface of the micro block 13 to pick up the micro block 13; the micro block 13 is placed on the supporting copper platform 30, as shown in FIG. Figure 4 As shown in (c), the microblock 13 is fixed to the supporting copper platform 30 by depositing metal platinum 14 on the microblock 13 and the supporting copper platform 30; the connection between the manipulator 20 and the microblock 13 is cut off by FIB, and the manipulator 20 is removed;

[0075] (3) Figure 4 As shown in (d), the microblock 13 is milled by FIB and gradually shaped to obtain the sample 10;

[0076] (4) The copper support 30 is fixed on the sample stage 2 , thereby achieving a fixed connection between the sample 10 and the sample stage 2 .

[0077] In some embodiments, the copper support 30 is bonded to the sample stage 2 by conductive silver glue to achieve connection between the sample and the sample stage.

[0078] In some embodiments, in step S2, the fixing fixture can be controlled to move in three directions on the base so that the J-shaped groove and the J-shaped connecting portion of the sample are coaxially aligned in a direction parallel to the sample stage bearing surface, and then the fixing fixture is moved in a direction parallel to the sample stage bearing surface and the base so that the J-shaped connecting portion of the sample is located in the J-shaped groove.

[0079] In some embodiments, in step S3, the loading drive mechanism is started, and when the sample is cyclically loaded with a bending load, the cyclic loading is performed according to a set loading function, and the loading function is F=Asin t, where A is an amplitude constant, and the amplitude of the bending load can be set according to different requirements, for example, 10, 15, 20, 25, etc., to study the bending fatigue deformation and failure behavior of the sample under different loading amplitudes.

[0080] In addition, before starting the loading drive mechanism for testing, the tip of the probe (i.e., the fixture) undergoes contact force calibration and zeroing to ensure the accuracy of the test. The tip of the probe in the bending fatigue test is the loading end of the fixture designed in the embodiment of the present invention.

[0081] In an embodiment of the present invention, SEM images of the sample can be collected in situ at different time points during the cyclic loading process of the sample, so as to analyze the evolution process of the bending fatigue morphology on the surface of the sample, the bending fatigue failure behavior and its microscopic mechanism based on the morphological changes of the sample in the SEM image during the cyclic loading process.

[0082] In some embodiments, software such as ImageJ can be used to measure particle size, shape, roughness, etc., and threshold segmentation techniques can be used to identify and segment different features in the image, such as cracks. The number of cracks per unit area of ​​the sample is calculated, and the distribution density of the cracks is recorded.

[0083] Furthermore, the measured features (such as particle size distribution, crack length, crack width, and distribution density) can be statistically analyzed, and statistical parameters such as mean and variance can be calculated to display the evolution of the morphology in a graphical form.

[0084] In addition, the initiation and propagation of cracks can be tracked in consecutive SEM images. For example, the crack propagation direction can be determined based on the geometric characteristics of the crack (e.g., the direction of the crack tip).

[0085] In some embodiments, the crack growth rate can be analyzed based on the change in crack length in the SEM images at different time points, where crack growth rate = ΔL / Δt, ΔL is the change in crack length, and Δt is the time interval.

[0086] In some embodiments, the fracture surface of the sample can also be observed, the morphology of the fracture surface can be analyzed, and the fracture mode of the material can be determined. Specifically, when the SEM image shows that there are many tearing edges and secondary cracks on the fracture surface of the sample, it indicates that the sample has cleavage fracture; when there are many dimples on the fracture surface, it indicates that the sample has dimple fracture.

[0087] The experimental method of the present invention can use FIB technology to prepare micrometer-scale in-situ bending fatigue specimens, carry out in-situ uniaxial cyclic loading experiments in SEM, and quantitatively analyze Ti 2 Microscopic mechanisms of deformation and failure of AlNb materials under cyclic loading.

[0088] The bending fatigue experimental research device and experimental research method of the present invention are further described below with reference to specific embodiments.

[0089] Example 1

[0090] like Figure 1 As shown, the experimental research device of this embodiment includes: a base 1, a sample stage 2 and an electron microscope device, the sample stage 2 is fixedly arranged on the base 1, the fixing fixture 3 is movably arranged on the base 1, the sample stage 2 and the fixing fixture 3 are spaced apart correspondingly, and the distance between the fixing fixture 3 and the base 1 is smaller than the distance between the sample stage 2 and the base 1.

[0091] The end of the fixing fixture 3 close to the sample stage 2 is formed with a loading end 5, which is made of diamond. The loading end 5 includes a main body 51 and an extension 52. The main body 51 is in a truncated cone shape, and the central axis of the main body 51 is perpendicular to the bearing surface of the sample stage 2. One end of the main body 51 is connected to the loading drive mechanism, and the other end is fixedly connected to the extension 52. The extension 52 is rectangular, and the extension 52 is perpendicular to the bearing surface of the sample stage 2 and is formed with a J-shaped groove 53 on one side away from the base 1.

[0092] Specifically, the opening of the J-shaped groove 53 is located at the side of the loading end 5 away from the base 1 and perpendicular to the bearing surface of the sample stage 2. The J-shaped groove 53 includes a first limiting groove, a second limiting groove and a third limiting groove. The first limiting groove is parallel to the third limiting groove, and the second limiting groove is perpendicular to the first limiting groove and the second limiting groove, respectively. The length direction of the second limiting groove is perpendicular to the bearing surface of the sample stage 2.

[0093] The sample stage 2 is used to support the sample 10, and its bearing surface is perpendicular to the base 1. When the sample 10 is connected to the sample stage 2, the first connecting section a and the third connecting section c of its connecting portion 12 are parallel to the bearing surface of the sample stage 2, and the second connecting end b is perpendicular to the bearing surface of the sample stage, so that the connecting portion 12 is matched and connected with the J-shaped groove.

[0094] The end of the fixing fixture 3 away from the sample stage 2 is connected to the loading drive mechanism, and the loading drive mechanism is used to drive the fixing fixture 3 to move back and forth in a direction perpendicular to the bearing surface of the sample stage 2, so as to apply a bending load perpendicular to the bearing surface of the sample stage to the end of the sample 10 connected to the fixing fixture 3, that is, to apply a bending load perpendicular to the length direction of the sample 10, so that the end of the sample 10 connected to the fixing fixture 3 can bend in two directions in a cyclical reciprocating manner, that is, bend in the direction toward and away from the bearing surface of the sample stage 2.

[0095] The force sensor 4 is connected between the fixing fixture 3 and the loading drive mechanism, and is used to detect the loaded bending load.

[0096] The electron microscope equipment is used to synchronously obtain the in-situ SEM image of the sample 10 during the bending fatigue test.

[0097] The above experimental research device is used to carry out bending fatigue experimental research. The specific process is as follows:

[0098] Step S1, prepare the sample and fix the sample on Figure 1 The sample stage of the experimental research apparatus is shown.

[0099] like Figure 4 As shown in (a), FIB is used to obtain Ti 2 Cubic microblocks 13 with a side length of about 20 μm are cut out from selected areas of the AlNb material.

[0100] like Figure 4 As shown in (b), in the FIB-SEM dual beam system, the robot arm 20 is micro-welded to the upper surface of the micro-block 13 to pick up the micro-block 13. Figure 4 As shown in (c), the microblock 13 is delivered to one side of the copper support 30 and fixed by depositing metal platinum Pt to form deposited metal platinum 14. The deposition current is 50pA, the voltage is 30kV, and the deposition thickness of the metal platinum is 20nm.

[0101] like Figure 4 As shown in (d), according to the set size of the sample, the connection portion 12 of the sample 10 is gradually formed by milling from different directions with a relatively low-energy ion beam, and finally a bending fatigue sample of set size is made. The set size includes: the length of the first connection segment is 12 μm, the width is 2.9 μm; the length of the second connection segment is 9.5 μm, the width is 3 μm; the length of the third connection segment is 5 μm, the width is 2 μm, and the fillet radius is 0.5 μm.

[0102] During the sample preparation, the FIB operating voltage was set to 30 kV, and the ion beam currents for rough and fine processing were set to 30 nA and 50 pA, respectively. Figure 5 As shown, it is consistent with the set size.

[0103] Finally, the copper support 30 is bonded to the sample stage 2 by conductive silver glue.

[0104] Step S2, moving the fixing fixture 3 so that the connecting portion 12 of the sample is connected to the J-shaped groove at the loading end of the fixing fixture.

[0105] Step S3, start the loading drive mechanism, as shown in the following example: Figure 6 As shown in the loading function, a bending load perpendicular to the length direction of the sample is applied to the sample, and cyclic loading is performed while collecting data from the force sensor and collecting SEM images of the sample in situ at different time points.

[0106] The specimen prepared in this embodiment has a compact structure and occupies a small space; and the specimen of this size can be stably connected to the fixing fixture. During the cyclic loading process of the bending fatigue test, no sliding or disengagement occurs, thereby ensuring the smooth progress and accuracy of the bending fatigue test.

[0107] In addition, the above-mentioned ion beam parameters and deposition parameters are used to process the sample with a processing accuracy of about 10nm. Not only is the sample of the set size prepared, but the surface of the sample is flat and smooth with a roughness of Ra 10nm, which meets the requirements of the in-situ bending fatigue experiment.

[0108] Comparative Example 1

[0109] The difference between this comparative example and Example 1 is that the processing of Ti 2 For AlNb samples, the ion beam current for finishing treatment is 100 pA. The surface of the sample prepared in this comparative example is relatively rough, with a roughness of Ra20 nm, resulting in poor surface quality.

[0110] Comparative Example 2

[0111] The difference between this comparative example and Example 1 is that when preparing the sample, the deposition thickness of metal platinum is 50 nm. The deposition thickness in this comparative example is too large, resulting in a large surface roughness of the sample after subsequent processing, which is Ra50 nm.

[0112] Comparative Example 3

[0113] The difference between this comparative example and Example 1 is that the deposition thickness of metal platinum is 15 nm. The deposition thickness of metal platinum in this comparative example is too small, resulting in the sample falling off from the copper support platform during the cyclic loading process.

[0114] Comparative Example 4

[0115] The difference between this comparative example and Example 1 is that the deposition current during the deposition of metal platinum is 100 pA. In this comparative example, the deposition current is too large, resulting in damage to the surface of the sample, and the roughness increases to Ra 100 nm.

[0116] Comparative Example 5

[0117] The difference between this comparative example and Example 1 is that the width of the first connection section of the J-shaped connection portion of the sample is 1.5 μm, the length of the second connection section is 5 μm, and the width of the third connection section is 1.5 μm. During the bending fatigue test, the sample slipped, resulting in inaccurate test results.

[0118] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A micro-nano-sized in-situ bending fatigue experimental research device suitable for Ti2AlNb materials, characterized in that: include: Electron microscope in-situ testing system, fixture, loading drive mechanism and force sensor; The electron microscope in-situ testing system comprises: a base, a sample stage and an electron microscope device, wherein the sample stage is fixedly arranged on the base, and the fixing fixture is movably arranged on the base; The sample stage and the fixing fixture are spaced apart from each other correspondingly, and the distance between the fixing fixture and the base is smaller than the distance between the sample stage and the base; The sample stage is used to carry a sample whose bearing surface is perpendicular to the base, one end of the sample is connected to the bearing surface of the sample stage, and the other end extends toward the base in a direction parallel to the bearing surface and is connected to the fixing fixture, so that the sample of Ti2AlNb material is connected between the sample stage and the fixing fixture, and the length direction of the sample is parallel to the bearing surface; One end of the fixing fixture away from the sample stage is connected to the loading drive mechanism, and is used to drive the fixing fixture to move back and forth in a direction perpendicular to the bearing surface, so as to apply a bending load perpendicular to the length direction of the sample to the sample; The force sensor is connected between the fixing fixture and the loading drive mechanism, and is used to detect the loaded bending load; The electron microscope equipment is used to synchronously obtain the in-situ SEM image of the sample during the bending fatigue test.

2. The experimental device according to claim 1, characterized in that: A loading end is formed at one end of the fixing fixture close to the sample stage, a J-shaped groove is formed at a side of the loading end away from the base, and an opening of the J-shaped groove is arranged at a side of the loading end away from the base and perpendicular to the sample stage bearing surface; the J-shaped groove includes a first limiting groove, a second limiting groove and a third limiting groove connected in sequence, and the length direction of the second limiting groove is perpendicular to the bearing surface of the sample stage; The sample comprises a sample body and a connecting portion, the connecting portion is J-shaped, the sample stage is used to fix the sample body, the connecting portion comprises a first connecting section, a second connecting section and a third connecting section, the first connecting section is connected to the sample body, the first connecting section is parallel to the third connecting section, and the second connecting section is vertically connected between the first connecting section and the third connecting section; when the sample is connected to the sample stage, the connecting portion is located on a side of the sample stage facing the base, and the second connecting section is perpendicular to the bearing surface; The J-shaped groove matches the shape and size of the connecting portion, and the J-shaped groove is used to install the connecting portion.

3. The experimental device according to claim 2, characterized in that: The loading end includes a main body and an extension portion, the main body is in a truncated cone shape, the central axis of the main body is perpendicular to the bearing surface of the sample stage, one end of the main body is connected to the loading drive mechanism, and the other end is fixedly connected to the extension portion, the extension portion is rectangular, and the J-shaped groove is formed on the side of the extension portion away from the base.

4. The experimental device according to claim 2, characterized in that: The length of the first connecting segment is 10-14 μm, the total length of the second connecting segment is 7.5-10.5 μm, and the length of the third connecting segment is 3.8-5.3 μm.

5. The experimental device according to claim 4, characterized in that: The length of the first connecting segment is 3.9 to 4.1 times the width of the second connecting segment, the total length of the second connecting segment is 1.9 to 2.1 times the length of the third connecting segment, and the length of the third connecting segment is 1.5 to 1.7 times the width of the second connecting segment.

6. A micro-nano-scale in-situ bending fatigue experimental research method suitable for Ti2AlNb materials, characterized in that: The method is implemented by using the experimental research device according to any one of claims 1 to 5, characterized in that it comprises: Step S1, preparing a sample of Ti2AlNb material, and installing the sample on the sample stage of the experimental device; wherein the length direction of the sample is parallel to the sample stage, and the J-shaped connecting portion of the sample extends out of the sample stage and toward the base; Step S2, moving the fixing fixture of the experimental device so that the connecting portion of the sample is connected to the J-shaped groove of the loading end of the experimental device; wherein the J-shaped groove is arranged on a side of the loading end away from the base, and its opening direction is away from the base and perpendicular to the sample stage; Step S3, starting the loading drive mechanism to drive the fixing fixture to move back and forth cyclically along the vertical direction of the sample stage bearing surface, so as to cyclically load the sample with a bending load perpendicular to the length direction of the sample, and at the same time collect data from the force sensor, and collect in-situ SEM images of the sample during the cyclic loading process; Step S4, analyzing the deformation and bending fatigue failure behavior of the sample under cyclic load according to the data of the force sensor and the SEM image.

7. The experimental method according to claim 6, characterized in that: The step S1 comprises: Using a focused ion beam to cut microblocks from selected areas of Ti2AlNb material; In a focused ion beam-scanning electron microscope dual beam system, the microblock is fixed on a supporting copper stage; Milling the microblock by the focused ion beam to gradually shape the sample into the sample, wherein the molded sample includes a sample body and a J-shaped connecting portion; The copper support platform is connected to the sample platform.

8. The experimental method according to claim 7, characterized in that: The focused ion beam milling of the microblock includes: using the focused ion beam to sequentially perform rough processing and fine processing on the microblock; wherein the ion beam current during the rough processing is 20-40nA, and the ion beam current during the fine processing is 40-60pA.

9. The experimental method according to claim 7, characterized in that: In the step S1, fixing the microblock on the supporting copper platform comprises: Metal platinum is deposited between the microblock and the copper support platform to fix the microblock to the copper support platform, and the deposition thickness of the metal platinum is 18-25 nm.

10. The experimental method according to claim 9, characterized in that: When depositing the metal platinum, the deposition current is 40-60 pA and the deposition voltage is 20-30 kV.